Analisis Rekrutmen Pegawai Negeri Sipil di Indonesia: Tantangan dan Peluang di Era Digital - Mario Tondi Partogi Lubis; Utari Tri Handayani; Nico Tri Aganta; Ritha F. Dalimunthe; Prihatin Lumbanraja (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Recruitment of State Civil Apparatus (ASN) in Indonesia has undergone significant transformation in recent years. The process that was previously dominated by manual mechanisms has now shifted to a digital-based system through the SSCASN platform. This article analyzes the implementation of ASN recruitment in 2024 with an emphasis on transparency, efficiency, and the challenges faced. Using a descriptive-qualitative approach, this article provides insight into how ASN recruitment can continue to be improved to meet the needs of public services in Indonesia.